Occurrence of Alleles of the HLA-A/B/C/DPB1/DQB1/DRB1 Genes in Autoimmune Hepatitis (Results of a Single-Center Study) - M. D. Chanyshev; Yu. G. Sandler; N. V. Vlasenko; N. A. Bodunova; A. G. Glushchenko; A. S. Chegodar; A. V. Vykhodtseva; E. V. Vinnitskaya; K. F. Khafizov; V. G. Akimkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
Aim: determination of alleles of HLA genes associated with autoimmune hepatitis (AIH) and overlap syndrome (OS) in the Russian population.Materials and methods. The study included 160 adult patients with a verified diagnosis of AIH or OS. The control group consisted of 320 conditionally healthy participants. A custom NGS panel was used to type the alleles of the HLA class I and II genes. The statistical analysis was carried out using Pearson’s χ2 test with multiple FDR correction (p < 0.05). A logistic regression model was used to evaluate HLA alleles as predictors of the disease.Results. Alleles and haplotypes which frequencies have statistically significant difference in the study and control groups were identified. In the study group, alleles HLA-A*01:01:01 (OR = 2.15; 95 % CI: 1.43–3.23), HLA-B*08:01:01 (OR = 3.38; 95 % CI: 2.10–5.44), HLA-C*07:01:01 (OR = 1.90; 95 % CI: 1.30–2.78), HLA-DPB1*01:01:01 (OR = 3.22; 95 % CI: 1.58–6.55), DQB1*02:01:01 (OR = 3.11; 95 % CI: 2.06–4.70), HLA-DRB1*03:01:01 (OR = 3.03; 95 % CI: 2.02–4.55) were more common. Frequency of occurrence of the DQB1*03:01:01 allele in the study group was lower than in the control group (OR = 0.49; 95 % CI: 0.34–0.71). A logistic regression model was built, which was characterized by an accuracy of 0.688, a sensitivity of 0.487, and a specificity of 0.887.Conclusion. Alleles and haplotypes of HLA genes associated with AIH and OS were identified in a representative sample of the Russian population.